New record of strawberry leopard ( Panthera pardus ) in Selous Game Reserve, Tanzania - Searle, CE; Strampelli, P; Parsais, SN; Haule, LJ; Olesyapa, KK; Salum, ND; Hape, G; Elisa, M; Mathayo, D; Kaduma, J; Malulu, N; Mkaka, N; et al. (Wiley Open Access, 2024)
Strawberry or red leopards are a rare colour morph of leopard (Panthera pardus) characterised by spot markings that are red or brown instead of black, thought to be a result of a mutation in the tyrosinase‐related protein (TYRP1) gene. We report the first record of this phenotype on the African continent outside of South Africa, from Selous Game Reserve in southern Tanzania. One female leopard with strawberry colouration was documented out of 373 individual leopards (0.3%) identified through camera trap surveys conducted from 2020 to 2022 over a combined area of more than 4600 km2 in the Nyerere‐Selous landscape.